A low exhaled nitric oxide level excludes a short‐term benefit from inhaled corticosteroids in suspected asthma: A randomized placebo‐controlled trial. Issue 7 (3rd May 2021) - Sutherland, Lissa; Shaw, Karen; Parrish, Clair; Singleton, Nicola; McKeever, Tricia M.; Stewart, Iain; Shaw, Dominick; Martin, Matthew J.; Harrison, Tim
Abstract: Background and objective: Fractional exhaled nitric oxide (FeNO) is a non‐invasive biomarker that reflects IL‐4/IL‐13 production and therefore represents T2 allergic inflammation. FeNO has previously been used to guide inhaled corticosteroid (ICS) treatment in asthma. The purpose of this study was to determine if a low FeNO (≤27 ppb) could be used to reliably identify patients with symptoms suggestive of asthma who would not benefit from initiating treatment with an ICS. Methods: A total of 180 steroid‐naïve adults with healthcare professional suspected asthma and an FeNO of ≤27 ppb were randomized to receive either 400 mcg of budesonide or placebo daily for 3 months. The primary outcome was the difference in the Asthma Control Questionnaire 7 (ACQ7) between treatment groups and the study was powered to determine equivalence. Secondary outcomes were the difference in FEV1, Medical Research Council and Leicester Cough Questionnaire scores. Results: One hundred and thirty‐four patients (68 budesonide and 66 placebo) completed the study and were included in the analysis. The between‐group mean difference in ACQ7 from baseline to the end of the study was −0.25 and the 95% CI around this difference was −0.004 to 0.495 confirming equivalence ( p  < 0.05). Differences in forced expiratory volume over 1 s and other secondary outcomes were also small and clinically unimportant. Conclusion: The results of this study suggest that steroid‐naïve patients with symptoms suggestive of asthma and an FeNO ≤ 27 ppb are unlikely to benefit from initiating treatment with an ICS over 3 months. However, further research is recommended to confirm these findings before withholding ICS treatment. Abstract : We conducted a randomized, double‐blind placebo‐controlled trial and demonstrated that steroid‐naïve patients with symptoms suggestive of asthma and a fractional exhaled nitric oxide level ≤ 27 parts per billion (ppb) are unlikely to benefit from treatment with an inhaled corticosteroid over 3 months. See related Editorial